Simulation of the Fast Pyrolysis of Coffee Ground in a Tilted-Slide Reactor - Sang Kyu Choi; Yeon Seok Choi; Yeon Woo Jeong; So Young Han; Quynh Van Nguyen (Energies, 2020)
The fast pyrolysis of coffee ground for bio-crude oil production was simulated in a tilted-slide reactor. The biochemical composition was derived by an extended biomass characterization method based on the elemental analysis. The simulation was performed in a steady-state and a Lagrangian multiphase model was adopted to describe the transport of sand and biomass particles together with a multistep kinetic mechanism for fast pyrolysis. When the secondary tar cracking reactions were not considered the volatile yield increased monotonically with temperature. The inclusion of secondary reactions could improve the prediction of volatile yield which turn to decrease at higher temperature. It was found that not only the maximum volatile yield but also the corresponding reactor temperature agreed well with the experimental results. At the temperature higher than 550 °C the trend of volatile yield is similar to that of experiment while it is larger at lower reactor temperature. The individual species yields were compared at various reactor temperatures and the pyrolysis processes were analyzed by tracking the reference components when they were decomposed along the distance. It was found that the reactor temperature should be above 500 °C for effective pyrolysis of all reference components of coffee ground.